Model "Policemen and thieves" - Felinskas, Gražvydas (Lietuvos matematikos rinkinys, 1998)
The article discusses "Policemen and Thieves" model similar to exclusion process. The theorem about invariant measures of the process has been proved and hydrodynamic behavior has been discussed.